Mediji in spremembe v literarnem sistemu - Kos, Dejan (Primerjalna književnost, 2017)
The concept of media refers to a complex phenomenological sphere. Relations between technological means and semiotic systems that are an integral part of enduring social, cultural, and communicative contexts are central to it. Media's influence on literature can therefore be comprehensively considered only if we also understand the latter as a complex social, cultural, and communications system. This article focuses on fundamental divisions in media history - written, print, and audio-visual media - and finds that in all instances, communications technologies suffuse the constitutive components of the literary system: its structures, symbolic order, and aesthetic conventions. From a structural point of view, media influence the definition of social roles and reorganization of cognitive systems. On the level of symbolic order, they influence the establishment of self-reflexive identity. The literary conventions of fictiveness and ambiguity also follow the logic of de- or reconstruction that typify manuscript, print, and audio-visual communication. In a systems approach, we best approximate an understanding of the literary field's organization when we focus on the mechanisms of mutual effects of all four components.
Keywords: audio-visual media; avdiovizualni mediji; communication technology; komunikacijska tehnologija; literarni sistem; literary system; literatura in mediji; literature and media; pisna kultura; print; printing; tisk; written culture